Pengembangan Aplikasi e-Dawlat Ikatan Pesantren Indonesia (IPI) dengan Pendekatan Rational Unified Process - Subandi; Muhammad Hidayat; Dirsa Arindra Septian (Ikatan Ahli Informatika Indonesia, 2024)
This research developed the e-Dawlat application, an Android-based mobile platform designed to facilitate the management and mapping of Boarding school, data in the South Kalimantan region. This application aims to improve efficiency and accuracy in disseminating information related to boarding school, to the community. Application development was carried out using PHP in the Laravel framework and Java in Android Studio, with MySQL database support. The Rational Unified Process (RUP) method was used in the development of this application to ensure a structured and iterative process, including system analysis, design, and implementation. The results of this research include the design of six database tables that support various processes in the application, as well as the development of 20 user interfaces to facilitate access to the various menus. The e-Dawlat application was tested using the black-box testing method, which resulted in satisfactory performance. In addition, the usability measurement shows a score of 89.86%, which indicates that this application is very feasible to be used by boarding school, administrators, students, and prospective students. With the ability to display data in real-time and interactively, this application allows quick and easy access to information, anytime and anywhere. The e-Dawlat application is expected to be an innovative solution in supporting the role of the Indonesian Pesantren Association (IPI) South Kalimantan in managing and disseminating information more effectively and responsively to technological developments.